STRUKTUR KEPEMILIKAN DAN KONSERVATISME AKUNTANSI - Krismiaji Krismiaji (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2020)
This research investigates the effect of ownership structure on accounting conservatism in companies listed on the Indonesia Stock Exchange from 2016 to 2018. The sampling was carried out using a purposive method and produced a sample of 149 companies with a total of 447 company-year observations. Conservatism is measured using the accrual method while ownership structure is calculated using the Herfindahl index. This study obtained evidence that concentrated ownership structure positively affects accounting conservatism. This research contributes to the literature by introducing a hybrid approach in the form of the Herfindahl index in measuring the density or density of share ownership.